The Private Value of Entrepreneurial Control: Evidence from a Discrete Choice Experiment - Berger, Marius; Doherr, Thorsten; Gottschalk, Sandra; Pellens, Maikel (The Review of Corporate Finance Studies, 2025)
Abstract We study how much entrepreneurs value control rights in the context of VC financing. While many entrepreneurs prefer to maintain control, transferring control rights is also central to VC contract design. Through a discrete choice experiment, we show that entrepreneurs have a high willingness to pay, 37% of the equity value of the venture, to avoid giving up control to investors, which we operationalize as giving investors a voting majority. Furthermore, control rights are valued higher than VC value-adding activities. Our findings imply that control considerations in VC contracts may create substantial trade-offs that deter entrepreneurs from VC financing. (JEL G24, L26, G32)